International directory of company histories. Volume 171. - Grant, Tina; Gale Group (Farmington Hills, Mich. St. James Press, a part of Gale, Cengage Learning, 2015)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.
4M Building Solutions, Inc. -- Abano Healthcare Group Ltd. -- African Oxygen Ltd. -- American Farm Bureau Federation -- Andino Investment Holding S.A. -- Aruba Networks, Inc. -- Banks Holdings Ltd. -- The Barbados Light and Power Company Ltd. -- BlueTie, Inc. -- CIMOS d.d. Avtomobilska industrija -- Comau S.p.A. -- Cotecna S.A. -- Cotton Buds, Inc. -- Criteo S.A. -- The Daily Beast Company LLC -- Detroit Institute of Arts -- Dole & Bailey Inc. -- Eggers & Franke Holding -- GmbH -- Fater SpA -- Forbo Holding AG -- Free State Brewing Co., Inc. -- Friedhelm Loh Group -- Fristads Kansas AB -- Gerolsteiner Brunnen -- GmbH & Co. KG -- Glorious Sun Enterprises Ltd. -- Grammer AG -- Groupe Loret -- Hana Microelectronics PCL -- Huf Hulsbeck & Furst -- GmbH & Co. KG -- The Humane Society of the United States -- Hunt Brothers Pizza LLC -- IAC Acoustics -- Indianapolis Motor Speedway Corporation -- Iplom S.p.A. -- Israel Chemicals Ltd. -- Jack in the Box Inc. -- JAKKS Pacific, Inc. -- Jasa Marga PT -- The Jaynes Companies Inc. -- Jersey Mike's Franchise Systems, Inc. -- Johnsonville Sausage L.L.C. -- Jones Soda Company -- Joseph Enterprises Inc. -- Jurys Inn Group Ltd. -- K-Swiss Inc. -- Kansai Paint Company Ltd. -- Kelda Group Ltd. -- Kelley Blue Book Company, Inc. -- Kerry Properties Limited -- Koch Enterprises, Inc. -- Konig Brauerei GmbH -- Kyowa Hakko Kirin Co., Ltd. -- Lamar Advertising Company -- Lancair International, Inc. -- Legacy Bakehouse LLC -- Leupold & Stevens, Inc. -- Life is good, Inc. -- Long Trail Brewing Company -- LRI Holdings Inc. -- Lund Boat Company Inc. -- Marchesa Ltd. -- Martha Tilaar Group -- The Maschhoffs, Inc. -- Mazzetta Company LLC -- Melting Pot Restaurants Inc. -- Morgan Truck Body LLC -- New York Football Giants LLC -- Oragroup S.A. -- The Palmer Family of Companies, Inc. -- Pan-O-Gold Baking Company, Inc. -- Patriarch Partners LLC -- Phillips & Jordan, Inc. -- The Pictsweet Company -- Pivovarna Lasko, d.d. -- Plaid Pantries, Inc. -- Pride Mobility Products Corporation -- Purity Dairies, Inc. -- Rakon Ltd. -- Rochester Drug Cooperative, Inc. -- Ronco Holdings, Inc. -- Runza National, Inc. -- Sesame Workshop -- Smeal Fire Apparatus Company -- Stark Bro's Nurseries & Orchards Co. -- Stoel Rives LLP -- Stupp Bros., Inc. -- SweetWater Brewing Company, Inc. -- Synlait Milk Ltd. -- Systemax, Inc. -- Taco Mayo Franchise Systems Inc. -- Taubman Centers, Inc. -- Ted's Montana Grill, Inc. -- Tempur-Sealy International, Inc. -- Tijuana Flats Burrito Company, Inc. -- Tilted Kilt Franchise Operating LLC -- Troyer Foods, Inc. -- Umami Restaurant Group, LLC -- Watlow Electric Manufacturing Company -- Wetzel's Pretzels LLC -- Wing Tai Holdings Ltd.
Includes bibliographical references and indexes.
Keywords: Big business -- History -- Directories; Business enterprises -- History -- Directories; Corporations -- History -- Directories